Avoidance learning: a review of theoretical models and recent developments - Krypotos, Angelos-Miltiadis; Effting, Marieke; Kindt, Merel; Beckers, Tom (Frontiers in Behavioral Neuroscience, 2015)
Avoidance is a key characteristic of adaptive and maladaptive fear. Here, we review past and contemporary theories of avoidance learning. Based on the theories, experimental findings and clinical observations reviewed, we distill key principles of how adaptive and maladaptive avoidance behavior is acquired and maintained. We highlight clinical implications of avoidance learning theories and describe intervention strategies that could reduce maladaptive avoidance and prevent its return. We end with a brief overview of recent developments and avenues for further research.